2019
DOI: 10.1186/s12977-019-0468-z
|View full text |Cite
|
Sign up to set email alerts
|

Origin and recent expansion of an endogenous gammaretroviral lineage in domestic and wild canids

Abstract: Background Vertebrate genomes contain a record of retroviruses that invaded the germlines of ancestral hosts and are passed to offspring as endogenous retroviruses (ERVs). ERVs can impact host function since they contain the necessary sequences for expression within the host. Dogs are an important system for the study of disease and evolution, yet no substantiated reports of infectious retroviruses in dogs exist. Here, we utilized Illumina whole genome sequence data to assess the origin and evolut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 111 publications
3
32
0
Order By: Relevance
“…Complementation is not uncommon between XRV and ERV [81, 82], is well established for murine Intracisternal A-type Particle (IAP) [83] and has been reported for ERV expansion in canids [84]. Complementation requires that two different retroviruses are co-expressed in the same cell [85].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementation is not uncommon between XRV and ERV [81, 82], is well established for murine Intracisternal A-type Particle (IAP) [83] and has been reported for ERV expansion in canids [84]. Complementation requires that two different retroviruses are co-expressed in the same cell [85].…”
Section: Discussionmentioning
confidence: 99%
“…However, because we have evidence for recent expansion of Lineage A and B recombinants, we considered an alternative explanation; that env -deficient Lineage B CrERV was complemented with an intact Lineage A CrERV envelope glycoprotein allowing for germline infection. Complementation is not uncommon between XRV and ERV (Hanafusa 1965; Evans et al 2009), is well established for murine Intracisternal A-type Particle (IAP) (Dewannieux et al 2004) and has been reported for ERV expansion in canids (Halo et al 2019). Complementation requires that two different retroviruses are co-expressed in the same cell (Ali et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In cats infected by FeLV, a recombination between endogenous and exogenous viruses can generate strains with specific pathogenic capabilities (45). The canine genome displays only a low percentage (∼0.15%) of ERVs compared to other mammals (46,47), and this is mainly related to a low number of repetitive elements in the genome (48). Despite hematological malignancies are frequent in dogs, and retroviral particles have been reported both in lymphomas and cell lines (49,50), no exogenous retroviruses have been identified in dogs or any other canid so far.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of exogenous retroviruses and the low number of ERVs are quite surprising mainly because canine cells are known to enable the replication of noncanid exogenous retroviruses, and the canine genome lacks the functional retroviral restriction factor TRIM5α (51). Recent studies have proposed that the expansion of an endogenous gammaretroviral lineage might originate from an infection in canid ancestors, thereby supporting the potential existence of canine exogenous retroviruses (46,52). Further studies are needed to confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
“…The de-novo assembled reads resulted in 1,721,922 contigs, of which more than 90% (1,559,773) matched with the Canis lupus familiaris genome (Genbank assembly accession: with study suggesting that most canine ERVs lineages ceased replicating long ago (35)(36)(37)(38)(39).…”
Section: Rna Extraction From Purified Microbial Aliquots and Sequencingmentioning
confidence: 99%